The Effect of Digitalization on the Quality of Service and Customer Loyalty - Lulzim Shabani; Arbëresha Behluli; Fidan Qerimi; Fellanze Pula; Pranvera Dalloshi (Ital Publication, 2022)
This research aims to measure the effect of digitalization on service quality through the SERVQUAL model (tangibility, reliability, responsiveness, assurance, and empathy) and customer loyalty. Also, we analyze the relationship between customer loyalty and their demographics. A quantitative method was used to achieve the objectives through a structured questionnaire, where part of the research sample was 400 clients of Kosovo banks. Results show that digitalization positively affects service quality and customer loyalty based on the OLS model. According to the T-test, there was no significant difference in customer loyalty between the genders. There has been a significant difference in loyalty between clients’ ages following the one-way ANOVA test. According to the Kruskal Wallis test, it also resulted in a significant difference between levels of education. This study will provide banks with feedback on the importance of digitalization and its correlation with their customers’ quality of service and loyalty. In this form, they decide to make even greater investments in digitalization by satisfying customer demands and creating loyal customers. Doi: 10.28991/ESJ-2022-06-06-04 Full Text: PDF